Systemic inflammation in young adults is associated with abnormal lung function in middle age. - Ravi Kalhan; Betty T Tran; Laura A Colangelo; Sharon R Rosenberg; Kiang Liu; Bharat Thyagarajan; David R Jacobs; Lewis J Smith (PLoS ONE)
Background Systemic inflammation is associated with reduced lung function in both healthy individuals and those with chronic obstructive pulmonary disease (COPD). Whether systemic inflammation in healthy young adults is associated with future impairment in lung health is uncertain. Methodology/principal findings We evaluated the association between plasma fibrinogen and C-reactive protein (CRP) in young adults and lung function in the Coronary Artery Risk Development in Young Adults cohort study. Higher year 7 fibrinogen was associated with greater loss of forced vital capacity (FVC) between years 5 and 20 (439 mL in quartile 4 vs. 398 mL in quartile 1, P<0.001) and forced expiratory volume in 1 second (FEV(1)) (487 mL in quartile 4 vs. 446 mL in quartile 1, P<0.001) independent of cigarette smoking, body habitus, baseline lung function and demographic factors. Higher year 7 CRP was also associated with both greater loss of FVC (455 mL in quartile 4 vs. 390 mL in quartile 1, P<0.001) and FEV(1) (491 mL in quartile 4 vs. 442 mL in quartile 1, P = 0.001). Higher year 7 fibrinogen and CRP were associated with abnormal FVC at year 20 (odds ratio (OR) per standard deviation 1.51 (95% confidence interval (CI): 1.30-1.75) for fibrinogen and 1.35 (95% CI: 1.14-1.59) for CRP). Higher year 5 fibrinogen was additionally associated with abnormal FEV(1). A positive interaction was observed between pack-years cigarette smoking and year 7 CRP for the COPD endpoint, and among participants with greater than 10 pack-years of cigarette exposure, year 7 CRP was associated with greater odds of COPD at year 20 (OR per standard deviation 1.53 (95% CI: 1.08-2.16). Conclusion/significance Systemic inflammation in young adults is associated with abnormal lung function in middle age. In particular, elevated CRP may identify vulnerability to COPD among individuals who smoke. Trial registration ClinicalTrials.gov NCT00005130.